Зброя ХІІ – першої половини ХІІІ ст. ударно-рубаючої та ударно-дроблячої дії з теренів північної Буковини - Возний, Ігор (Ігор Возний. Зброя ХІІ – першої половини ХІІІ ст. ударно-рубаючої та ударно-дроблячої дії з теренів північної Буковини. Історія давньої зброї. Дослідження 2018. Збірник наукових праць Третьої міжнародної зброєзнавчої конференції (Київ, 12–14 червня 2018 р.) / упоряд. Д. В. Тоїчкін; Інститут історії України НАН України. Київ : Інститут історії України НАНУ, 2020. С. 37–50., 2020)
Ihor Vozny STR IKE -SLAS HING AND STR IKE -POUND ING WEA PONS OF the 12th – HAL F OF THE 13th CENTURY ON THE TERRITORY OF NORTHERN BUKOVYNA This article aims to study a slashing and pounding impact weapons that were found on archaeological sites of Old Rus in the area between the upper Prut and the middle Dniester. The author made a typological classified the medieval archaeological finds according to the common typology – axes, maces and knobsticks. The strike-chopping weapon of the melee were the battle-axes. By analyzing the samples of weapons discovered on the studied areas, it is possible to distinguish among them combat and universal axes, using the typology of Anatoly Kirpichnikov they can be attributed to types B, IVA and VA. An integral part of the armament of the warrior was a mace. Six iron and three bronze mace heads were found at the archaeological site. These maces can be classified as types І, ІІ, ІІА, ІV according to typology of Kirpichnikov. The melee strike weapon was the knobsticks as an auxiliary weapon of the combat. In the local museum, there is a fragment of a bone knobstick transmitted from Galich. It belongs to the type 1 (according to Kirpichnikov) and dated of 10-13 centuries. Thus, as the result of the analysis of the slashing and pounding impact weapons, the author concluded that the military art of the local population was developing in close contact with the other lands of the Old Rus state. Subsequently, the studying of the ancient weapons from the territories of Northern Bukovina will allow us to deepen our knowledges of the military affairs of the ancient Rus state in general.
Keywords: axe; mace; knobstick; strike-chopping weapon; strike-pounding weapon